2007
DOI: 10.1002/dat.20117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atherosclerosis and atherosclerotic risk factors in patients receiving hemodialysis and peritoneal dialysis

Abstract: BACKGROUND: Although some studies have found that myocardial infarction and cerebrovascular disease are more common in patients receiving continuous ambulatory peritoneal dialysis (CAPD) than in patients receiving hemodialysis (HD), the results of other studies have not supported these findings. Studies comparing patients receiving HD with patients receiving CAPD have had conflicting results.OBJECTIVE: The aims of this study were to compare the atherosclerotic changes in CAPD and HD patients and to assess whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…that changes in CCA are related to a disturbed lipid profile, primarily due to a reduced level of HDL and an increase in LDL. [ 32 ] We have confirmed that HDL represents a significant independent factor that influences the regression of CCA IMT in patients treated with CAPD, while LDL has a predictive influence on the rigidity of the CCA wall, assessed based on the CCA diameter. These results support the results of the Study of Heart and Renal Protection (SHARP) study[ 33 ] that lipid disorders should be aggressively treated in dialysis patients in order to reduce the risk of CVD and keep the LDL level below 3 mmol/L.…”
Section: Discussionsupporting
confidence: 55%
“…that changes in CCA are related to a disturbed lipid profile, primarily due to a reduced level of HDL and an increase in LDL. [ 32 ] We have confirmed that HDL represents a significant independent factor that influences the regression of CCA IMT in patients treated with CAPD, while LDL has a predictive influence on the rigidity of the CCA wall, assessed based on the CCA diameter. These results support the results of the Study of Heart and Renal Protection (SHARP) study[ 33 ] that lipid disorders should be aggressively treated in dialysis patients in order to reduce the risk of CVD and keep the LDL level below 3 mmol/L.…”
Section: Discussionsupporting
confidence: 55%
“…Currently, studies about dialysis impact on ultrasound measured cIMT have shown contradictory results. Despite all studies have found higher cIMT on dialysis patients than in non-dialysis population,(Cengiz and Dolu, 2007; Mutluay et al, 2012; Shi et al, 2012) some of them reported higher cIMT in PD than in HD (Ozdemir et al, 2001; Shi et al, 2012), some other did not find significant differences on cIMT between dialysis type (Cengiz and Dolu, 2007; Yilmaz et al, 2007; Al-Hweish et al, 2010), and some others reported increased cIMT in HD patients (Mutluay et al, 2012). However, it is important to remark that, in contrast to most previous studies, the NEFRONA study excluded patients with a previous CVE.…”
Section: Discussionmentioning
confidence: 91%